Cooperative Learning Transformation: Integration of Team Games Tournament and Deep Learning for Forming Humanist-Religious Character - Nia Paramita; Achmad Yusuf; Ahmad Marzuki; Muhammad Nur Hadi (Ta'dib, 2026)
This study aims to describe the innovative implementation of the Deep Learning-based Teams Games Tournament (TGT) model in Islamic Education (PAI) at SMKN 1 Purwosari, and to analyze its implications in shaping students' humanistic-religious character as an effort to mitigate the Three Major Sins of Education (bullying, sexual violence, and intolerance). A qualitative approach with a case study design was employed. Data collection involved participant observation, in-depth interviews with PAI teachers, students, and homeroom teachers, along with document analysis. Interactive data analysis consisted of data condensation, data display, and conclusion drawing, supported by technique, source, and time triangulation to ensure trustworthiness. The findings reveal that this instructional innovation is effectively realized through the 3M cycle (Feeling, Meaning-making, and Living) and the utilization of digital media like the Wheel of Names and smartphone exploration as active character research tools. Students' religious character is organically manifested through the internalization of Maqasid al-Shariah values, specifically Hifzh al-'Aql (preservation of intellect), while the humanistic character is forged through social solidarity and sportsmanship within heterogeneous group dynamics. The implications suggest that integrating digital technology (high-tech) with a humanistic touch (high-touch) establishes a resilient internal moral filter among students, thereby preventively mitigating violent behavior, bullying, and intolerance in vocational school environments.